Semiotics of Subtitle in the Iraqi Novel A study of selected samples - Jameel Abbas, Assist . Lect. Ammar; Oudah Hashin, Prof. Dr. Hussein (Basra studies journal, 2023)
The research attempted to shed light upon semiotics as a science by studying some samples of Iraqi novel subtitles. Through this study, the researchers gave definitions to semiotics, linguistically and idiomatically, and then dealt with the science of titling, also linguistically and idiomatically. This study highlighted the importance of semiotics for the study of Iraqi novel subtitles.